Perancangan Fasilitas Sleeping Box di area Tunggu Bandara Juanda â Terminal 2 - Sugianto, Stephanie (Intra, 2015)
Sleeping Box facilities in Wait Around Juanda Airport - Terminal 2 is designed to meet the needs of passengers who were waiting for hours when experiencing flight delay flight and transit. These facilities include all the necessities needed while waiting for passengers, among other amenities lying, sitting facilities, working facilities, entertainment facilities, and storage facilities. The concept used in this design is